Identifying Dimensions of Social Withdrawal in Academically Gifted Youth - Lee, Sophia; Anderson, Michael (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: This study aimed to explore the underlying dimensions of social withdrawal in academically gifted adolescents through a qualitative lens, focusing on emotional, social, academic, and behavioral factors. Methods and Materials: A qualitative research design was employed using semi-structured interviews with 27 academically gifted adolescents aged 12 to 18 years from various regions in the United States. Participants were selected through purposive sampling to ensure diversity in gender, ethnicity, and school setting. Data collection continued until theoretical saturation was reached. All interviews were transcribed verbatim and analyzed thematically using NVivo software, following a multi-stage coding process involving open, axial, and selective coding to extract key themes and subthemes. Findings: Thematic analysis revealed four main categories contributing to social withdrawal in gifted adolescents: emotional and psychological drivers, peer and social environment, academic and institutional context, and coping and withdrawal strategies. Subthemes included fear of rejection, perfectionism, social anxiety, peer mismatch, bullying, academic overload, and digital escape, among others. Participants described both internal vulnerabilities and external pressures leading to voluntary isolation. While some withdrawal behaviors were associated with emotional distress, others served as self-protective strategies to maintain control and authenticity in unsupportive environments. Quotations from participants illustrated the complexity and depth of these experiences. Conclusion: Social withdrawal in academically gifted youth is a multidimensional phenomenon shaped by a dynamic interaction between personal dispositions and environmental conditions. Recognizing both the risks and adaptive aspects of withdrawal is essential for designing responsive educational and psychological support systems.